Absorption of nasal and bronchial fluids: precision sampling of the human respiratory mucosa and laboratory processing of samples - Thwaites,RS; Jarvis,HC; Singh,N; Jha,A; Pritchard,A; Fan,H; Tunstall,T; Nanan,J; Nadel,S; Kon,OM; Openshaw,PJ; Hansel,TT (Jove-Journal of Visualized Experiments, 2018)
The methods of nasal absorption (NA) and bronchial absorption (BA) use synthetic absorptive matrices (SAM) to absorb the mucosal lining fluid (MLF) of the human respiratory tract. NA is a non-invasive technique which absorbs fluid from the inferior turbinate, and causes minimal discomfort. NA has yielded reproducible results with the ability to frequently repeat sampling of the upper airway. By comparison, alternative methods of sampling the respiratory mucosa, such as nasopharyngeal aspiration (NPA) and conventional swabbing, are more invasive and may result in greater data variability. Other methods have limitations, for instance, biopsies and bronchial procedures are invasive, sputum contains many dead and dying cells and requires liquefaction, exhaled breath condensate (EBC) contains water and saliva, and lavage samples are dilute and variable. BA can be performed through the working channel of a bronchoscope in clinic. Sampling is well tolerated and can be conducted at multiple sites in the airway. BA results in MLF samples being less dilute than bronchoalveolar lavage (BAL) samples. This article demonstrates the techniques of NA and BA, as well as the laboratory processing of the resulting samples, which can be tailored to the desired downstream biomarker being measured. These absorption techniques are useful alternatives to the conventional sampling techniques used in clinical respiratory research.